Mathematical Modeling of Online Transaction Processing System for Design of Building Territory - Honcharenko, Tetyana; Kyivska, Kateryna; Liashchenko, Mariia; Terentyev, Oleksandr; Gorbatyuk, Ievgenii; Dolya, Elena (2021 IEEE 3rd Ukraine Conference on Electrical and Computer Engineering (UKRCON), 2021)
This study is devoted to the problem of the ability to represent multidimensional design of building territory based on Online Analytical Processing (OLAP) technology. Building territory is viewed as complex information system, which relate with other information systems of surrounding areas. Mathematical modeling of such information system for multidimensional design based on OLAP technology is proposed to solve this problem. It is proposed to use a Online Transaction Processing (OLTP) system for multidimensional analysis and design of the two subject areas. The first subject area contains background information about the topography, geodesy and geology of the building territory. The second subject area contains information about the surrounding areas to the building territory. OLAP cubes represent multidimensional information objects with associated properties. Each OLTP system is an implementation of a domain model and is designed by a multidimensional matrix, which is represented as an OLAP cube. The application of this concept in a Web-based environment is covered.